First report of papaya ringspot virus w infecting momordica charantia in Cuba - Cabrera Mederos, Dariel; Giolitti, Fabian; Portal, O. (Dipartimento di Scienze del Suolo, della Pianta e degli Alimenti, Università di Bari, 2021)
During a survey conducted in July 2010, severe mosaic and deformations were observed on the leaves of cerasee (Momordica charantia) in Villa Clara, Cuba. The symptoms resembled those induced by Papaya ringspot virus (PRSV) in papaya (Carica papaya L.) plants (Olarte et al., 2011). Leaf samples were ELISA positive when tested with a specific PRSV antiserum (Agdia, USA). The presence of PRSV was confirmed by the amplification of a 850 bp fragment by RT-PCR using primers specific to the PRSV coat protein gene (unpublished information). BLASTn analysis of the sequences from the RT-PCR amplified product (GenBank accession No. KP019380) showed 94% identity with PRSV-W isolates from Citrullus lanatus in the USA (GenBank accession Nos. JN132439 to JN132457) and PRSV-P isolates (GenBank accession Nos. AF196839 and EF189736). Crude sap extracts from symptomatic M. charantia leaf samples were mechanically inoculated onto Cucurbita moschata and papaya plants. Symptoms developed in the former but not in the latter plants, suggesting the presence of PRSV-W, since only PRSV-P is able to infect papaya plants (Romay et al., 2014). In inoculated plants, the presence of this virus was determined by ELISA. In Cuba, the first molecular detection of PRSV-W was from Cucurbita pepo (Rodríguez- Martínez, personal communication) and PRSV-P has only been reported in papaya plants (Portal et al., 2006). To our knowledge, this is the first report of PRSV-W infecting M. charantia in Cuba. This finding is relevant for the epidemiology, and management of this disease in cucurbits.